Democratic Republic of Sao Tome and Principe : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of Sao Tome and Principe. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses a request from the Democratic Republic of Sao Tome and Principe for a three-year arrangement under the Poverty Reduction and Growth Facility (PRGF). The economic outlook for 2009 is broadly favorable, but subject to significant risks. The program spans a period including major elections; the authorities' ability to meet fiscal objectives and implement monetary policy will be key to the success of the program. IMF staff recommends approval of the new PRGF arrangement based on the country's policy commitments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet